2018
DOI: 10.1016/j.midw.2018.01.005
|View full text |Cite
|
Sign up to set email alerts
|

The use of drama within midwifery education to facilitate the understanding of professional behaviour and values

Abstract: the students felt that the move away from a didactic approach to learning and teaching towards a more experiential model of teaching, enabled a more in depth reflection on the importance of professional standards and behaviour when providing care to pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Through drama, a writer can maintain the circulation of the development of language ideology (Robertson, 2019). Practising acting in a drama can help make for positive behaviour in certain professions (Lawrence & Wier, 2018). Playing in a drama is not much different from playing music because it can increase the activity of the hypothalamus, brainstem, and anterior cerebellum when imagining scriptbased scenes (Li et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Through drama, a writer can maintain the circulation of the development of language ideology (Robertson, 2019). Practising acting in a drama can help make for positive behaviour in certain professions (Lawrence & Wier, 2018). Playing in a drama is not much different from playing music because it can increase the activity of the hypothalamus, brainstem, and anterior cerebellum when imagining scriptbased scenes (Li et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to maternal health, theatre and role play have been used as part of midwifery training, to challenge midwifery students to explore the perspectives of patients and reflect on the care they provide to mothers in the UK 23 24. In such studies, midwifery students were supportive of the idea of collaborative projects and felt that the move away from a didactic approach to learning and teaching towards a more experiential model of teaching, enabled a more in-depth reflection on the importance of professional standards and behaviour when providing care to pregnant women 23 24. However, the theatre-based interventions used in these studies have not been evaluated to demonstrate the impact on the midwifery student’s overall learning.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of a study evaluating the impact of creative drama method on the adoption of professional values for midwifery students, it was found that creative drama facilitates students to learn professional values. Furthermore, in addition to the development of professional values, the study set out that the knowledge experienced by living affects positively the communication with pregnant women during the practices 27 . There are various practice examples in the literature that can improve empathic skills for midwives 28 and nurse students 29 .…”
Section: Figure 1 Self-esteem Levels Of Students As Per the Rosenberg Self-esteem Scale Pre And Post Creative Drama Educationmentioning
confidence: 99%
“…Creative drama is a method that contributes significantly to the evolvement of one's self-esteem. Creative drama helps individuals increase their self-esteem by knowing themselves in their professional and social lives, recognizing their competencies, developing a sense of appreciation or approval 27 . A study conducted to evaluate the effects of creative drama course on child development department students' (n=87) self-esteem established that the scores of self-perception showed a statistically significant difference and that creative drama education enabled the increase of self-perception 22 .…”
Section: Figure 1 Self-esteem Levels Of Students As Per the Rosenberg Self-esteem Scale Pre And Post Creative Drama Educationmentioning
confidence: 99%